2020
DOI: 10.11137/2020_1_355_365
|View full text |Cite
|
Sign up to set email alerts
|

Air Temperature and Precipitation Climatologies over Paraíba Sul River Basin, Southeast Brazil

Abstract: Este trabalho analisa as climatologias da temperatura do ar e da precipitação da Bacia do rio Paraíba do Sul (BRPS), localizada na Região Sudeste do Brasil. A precipitação anual varia entre 1000 mm no norte do estado do Rio de Janeiro e 2000 mm sobre a Serra da Mantiqueira. Aproximadamente 80% da precipitação da bacia concentra-se nos meses de outubro a março, sugerindo um regime monçônico na região. A média anual da temperatura média diária varia entre 16°C no extremo sudoeste e 22°C no extremo norte da BRPS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
3
3
0
2
Order By: Relevance
“…The highest average annual values of accumulated precipitation were recorded in mountainous regions, such as Fazenda Agulhas Negras with 2385 mm (1242 m) and Visconde de Mauá with 2234 mm (1030 m), both in the Serra da Mantiqueira, a mountainous region. These results agree with those presented by [47] who associated higher precipitation values with sites located at altitudes higher than 2000 m. However, the region of the Baixo Paraíba do Sul, located in the north and northwest of Rio de Janeiro, and characterized as a depression region, registers annual precipitation values below 1000 mm/year (Figure 1). The difference in annual accumulated values of precipitation can be associated on a broader scale by the valley-mountain circulation, where precipitation occurs due to orographic forcing and Figure 3 displays the spatial distribution of p95 and p99 thresholds for extreme and very extreme rainfall events during the dry and wet seasons.…”
Section: Precipitation Data Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…The highest average annual values of accumulated precipitation were recorded in mountainous regions, such as Fazenda Agulhas Negras with 2385 mm (1242 m) and Visconde de Mauá with 2234 mm (1030 m), both in the Serra da Mantiqueira, a mountainous region. These results agree with those presented by [47] who associated higher precipitation values with sites located at altitudes higher than 2000 m. However, the region of the Baixo Paraíba do Sul, located in the north and northwest of Rio de Janeiro, and characterized as a depression region, registers annual precipitation values below 1000 mm/year (Figure 1). The difference in annual accumulated values of precipitation can be associated on a broader scale by the valley-mountain circulation, where precipitation occurs due to orographic forcing and Figure 3 displays the spatial distribution of p95 and p99 thresholds for extreme and very extreme rainfall events during the dry and wet seasons.…”
Section: Precipitation Data Analysissupporting
confidence: 92%
“…The difference in annual accumulated values of precipitation can be associated on a broader scale by the valley-mountain circulation, where precipitation occurs due to orographic forcing and presents an intense gradient towards regions with higher altitudes. The spatial precipitation patterns are in line with the results of [19,47], through different datasets. The box plot shows the annual accumulated precipitation values in the PSRB from 1939 to 2020 in Figure 2b.…”
Section: Precipitation Data Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…The region presents a seasonal precipitation variability, with a well defined rainy and dry season, associated with the South America Monsoon System (Reboita et al, 2010). In winter (end of June to end of September), the accumulated precipitation does not exceed 200 mm and in summer the values reach 800 mm (Brasiliense et al, 2020). Ayres (2010) showed that floods and severe storms have a high frequency in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Com a variabilidade climática e o agravamento das crises hídricas, diversos setores da sociedade, como as atividades agropecuárias e industriais, geração de energia, são prejudicadas, resultando em riscos para o meio ambiente, a saúde humana e a queda da qualidade de vida (Brasiliense et al, 2020;Mendes, 2022;Schilling et al, 2020). O Sul do Brasil é a região mais vulnerável aos desastres desencadeados por chuvas extremas, em destaque às regiões metropolitanas com alto desenvolvimento econômico e alta densidade populacional urbana (Marengo et al, 2021).…”
Section: Introductionunclassified